Giải pháp phát triển hoạt động kinh doanh thẻ tín dụng tại ngân hàng TMCP Sài Gòn Thương Tín - Chi nhánh Thanh Trì / Nguyễn Thị Bích Ngọc; Vũ Thị Thục Oanh - Nguyễn, Thị Bích Ngọc
ĐTTS ghi: Trường ĐHKTKTCN